PEMILIHAN MODA TRANSPORTASI MENUJU SEKOLAH PELAJAR SMA NEGERI 6 KOTA PALEMBANG - Hariman Al Faritzie; Felly Misdalena; Dian Astria Z; Verinazul Septriansyah (LATERAL: Jurnal Teknik Sipil, 2023)
Transportation is a very important aspect in the framework of economic development in a region, Transportation is also a necessity for many elements of society including the needs for students. Transportation plays an important role in the process of improving education. To reach school, students can use various types of transportation modes. Based on the current condition, the Sekip Ujung Flyover construction project is currently underway on the Basuki Rahmat road, this study aims to find out how the characteristics of SMA Negeri 6 Kota Palembang students in determining the mode of transportation used to go to school and how the dominant mode of transportation is used by SMA Negeri 6 Kota Palembang students to go to school. By using cross-tabulation analysis, the results of the analysis obtained are that the factors that influence respondents in choosing a mode of transportation to school.factor is travel time, with the proportion of respondents as much as 32%. The most dominant type of mode chosen by students of SMA Negeri 6 Kota Palembang to go to school is using online transportation. Online transportation was chosen because it is another alternative mode selection because it is easy to access.